2012
DOI: 10.7824/rbh.v11i1.129
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade da matéria prima de cultivares de cana-de-açúcar submetida à aplicação de herbicidas

Abstract: Resumo-Os herbicidas podem causar intoxicação à cultura e também efeitos negativos nas características produtivas e na qualidade industrial da cana-de-açúcar. Neste trabalho avaliou-se os efeitos dos herbicidas ametryn, trifloxysulfuron-sodium, ametryn + trifloxysulfuron-sodium e sulfentrazone sobre a qualidade e produtividade de colmos das cultivares RB867515, SP801816, SP803280, RB937570 e RB925211. O experimento foi conduzido na área experimental da Universidade Federal de Viçosa, Viçosa-MG. Observou-se com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(31 reference statements)
0
1
0
1
Order By: Relevance
“…However, Tironi et al (2012) found reduced productivity (TCH --tons of sugarcane per hectare) when herbicides were applied at post-emergence of sugarcane (three to four fully expanded leaves). Thus, it is recommended the morning glory control at the first application, even PPI more than 70 DAE.…”
Section: Resultsmentioning
confidence: 99%
“…However, Tironi et al (2012) found reduced productivity (TCH --tons of sugarcane per hectare) when herbicides were applied at post-emergence of sugarcane (three to four fully expanded leaves). Thus, it is recommended the morning glory control at the first application, even PPI more than 70 DAE.…”
Section: Resultsmentioning
confidence: 99%
“…Ressalta-se que, na condição desse experimento, nem mesmo a aplicação isolada do herbicida sulfentrazone diminuiu a produtividade da cultura de cana-de-açúcar. Esse trabalho está em concordância com Tironi et al (2012), que ao realizarem a pulverização de 750 g ha -1…”
Section: Produção De Colmosunclassified